KARAKTERISTIK BRIKET BIOARANG KOMBINASI PELEPAH DAN TANDAN KOSONG KELAPA SAWIT (ELAEIS GUINEENSIS JACQ.) - Triwibowo, Radez Triwibowo; Johan, Vonny Setiaries; Hamzah, Farida Hanum (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
The purpose of this study was to obtain the best combination of midribs and oil palm empty fruit bunches on the characteristics of bioarang briquettes produced. The study was conducted experimentally using a completely randomized design (RAL) with five treatments and three replications, in order to obtain 15 units. The treatment in this study is the difference of percentage midribs and oil palm empty fruit bunches, namely (P1 = 25% : 65%, P 2= 35%: 55%, P3 = 45%: 45%, P4 = 55%: 35%, and P5 = 65%: 25%), with 10% tapioca adhesive. The analysis tested in this study were water content, ash content, volatile substance content, carbon rate, and heating value. The results of variance showed that the percentage of midribs and oil palm empty bunches gave a significant effect on water content, volatile substance content, ash content, carbon rate, and heating value. The best formulation selected was P1 25% midrib and 65% oil palm empty bunches with water content of 6.79%, volatile substance content 8.99%, ash content 9.51%, carbon rate 74.70%, and heating value 5742.80 kal/g.